Boundary PID Control for the Temperature of Chemical Pipeline Fluid - Liu, Chunxiao; Gong, Dexin; Wang, Mi (International Journal of Natural Resources and Environmental Studies, 2026)
In chemical production, the accuracy of pipeline fluid temperature control is very important for ensuring product quality, improving production efficiency and ensuring production safety. In this paper, the design and implementation of chemical pipeline fluid temperature control system based on boundary proportional-integral-derivative (PID) control algorithm are deeply discussed. Firstly, the principle of PID control algorithm and its advantages in the field of temperature control are expounded in detail. Secondly, according to the specific requirements of chemical pipeline fluid temperature control, the boundary PID control architecture is proposed and the key advantages are analyzed in detail. Finally, the effectiveness of the proposed control method is verified by simulation experiments. The results show that the system based on boundary PID control can respond quickly and achieve the goal of fluid temperature control, which provides reliable technical support for chemical production.